Cassava technology transfer and utilization in India - Balagopalan, C.; Anantharaman, M. (International Center for Tropical Agriculture, 1995)
The average cassava yield of 21 t/ha in India compares favorably with a world average of 10 t/ha. On-farm trials have revealed that it is possible to increase yields to more than 30t/ha through more intensive management. The Cassava Technology Transfer Programme (CTTP) in India has passed through various phases, concentrating mainly on production technologies and of late on processing technologies. CTTP started in the early 1970s with the release of high-yielding varieties of cassava (HYVC) and by conducting National Demonstrations in farmers' fields. These indicated that HYVC with intensive management could produce yields of more than 35 t/ha. During 1976, CTCRI (with financial assistance from IDRC) implemented an Operational Research Project in a village near Trivandrum with the main objective of identifying operational constraints faced by small farmers adopting cassava production technologies. In 1979 CTCRI implemented the Lab-to-Land Programme (LLP) of ICAR, with the main aim of creating a direct linkage between technology generators and small and marginal farmers. This program has directly benefitted more than 1000 farmers in 14 villages of three states. The LLP initially gave emphasis to production technologies, but is now also concentrating on transferring processing technologies by a series of demonstrations and training programs. All these CTTP attempts have proved effective in terms of increasing the adoption level of cassava technology by more than 40% of the farmers. The transfer of technologies to a larger mass was also attempted through a functional linkage with development departments through systematic training programs in order to equip the extension personnel with the latest technologies in cassava production. Besides the efforts made by CTCRI, the State Departments of Agriculture through their extension network are engaged in the transfer of technology through demonstrations and farmers' training programs. The socio-economic impact of CTTP is very encouraging considering that a) cassava yields in the country have increased at an annual rate of about 1% since 1970; b) the HYVC have diffused to more than three fourth of the cassava area in Tamil Nadu and Andhra Pradesh and to some pockets of Kerala; c) the majority of farmers have accepted most of the recommended practices. The transfer of technology in the case of processing and utilization of cassava could not be done in an effective manner for want of an organized extension system for processing technologies. However, attempts are being made to diffuse the developed products and processing technologies through the Lab-to-Land Programmes, public exhibitions, food festivals, farmers' meetings etc.